Foetal Macrosomia and Foetal-Maternal Outcomes at Birth - Sahruh Turkmen; Simona Johansson; Marju Dahmoun (Journal of Pregnancy, 2018)
To investigate how macrosomia affects foetal-maternal birth outcomes, we conducted a retrospective cohort study of singleton pregnant women who gave birth at gestational age ≥37+0 weeks. The patients were divided into three groups according to birth weight: “macrosomia” group, ≥4500 g, n=285; “upper-normal” group, 3500–4499 g, n=593; and “normal” group, 2500–3499 g, n=495. Foetal-maternal and delivery outcomes were compared among the three groups after adjustment for confounders. Caesarean section was more frequent in the macrosomia group than in upper-normal and normal groups. The duration of labour (p < 0.05) and postpartum care at the hospital (p < 0.001) were the highest in the macrosomia group. Increased birth weight was associated with higher risks of shoulder dystocia (p < 0.001), increased bleeding volume (p < 0.001), and perineal tear (p < 0.05). The Apgar score at 5 minutes (p < 0.05), arterial cord pH (p < 0.001), and partial pressure of O2 (p < 0.05) were lower, while the arterial cord partial pressure of CO2 was higher (p < 0.001), in the macrosomia group. Macrosomia has potentially serious impacts for neonate and mother as a result of a complicated and occasionally traumatic delivery.